2011
DOI: 10.1111/j.1465-7295.2011.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Double Majors: One for Me, One for the Parents?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Parental Influence: A couple of papers have examined the role played by parents on the choice of college major. Notably, Zafar (2012Zafar ( , 2013 addresses this question using subjective expectations data collected from a sample of sophomores from Northwestern University.…”
Section: Other Determinantsmentioning
confidence: 99%
“…Parental Influence: A couple of papers have examined the role played by parents on the choice of college major. Notably, Zafar (2012Zafar ( , 2013 addresses this question using subjective expectations data collected from a sample of sophomores from Northwestern University.…”
Section: Other Determinantsmentioning
confidence: 99%
“…1 Pitt and Tepper (2012) find that the partnering of economics with math, political science, foreign language, other business majors, and engineering comprise five of the top ten undergraduate double majors. Zafar (2012) finds that at least part of students' decision to double major is based on expectations that their major combinations will positively impact their chances of degree completion and finding a job after graduation. Del Hersch (2008, 2016) and Hemelt (2009) find that double majoring is associated with higher earnings and better job matches relative to graduating with a single major, provided that the double majors are across rather than within general disciplinary groups and also when the second major is in a relatively technical or high paying field.…”
Section: This Paper Documents Trends In Disciplines' Shares Of First mentioning
confidence: 99%
“…Dominitz and Manski sequentially elicited 13. These include Arcidiacono et al (2012), Giustinelli (forthcoming), Stinebrickner (2012, 2014), Wiswall andZafar (2015a, 2015b), and Zafar (2011and Zafar ( , 2013, some of which we describe further below.…”
Section: A Assumptions Versus Measurement Of Subjective Expectationsmentioning
confidence: 99%
“…Rouse (2004) elicits subjective median earnings expectations with and without a college degree from a sample of high school seniors in Baltimore. Zafar (2013Zafar ( , 2011) elicits probabilistic expectations regarding the monetary and nonmonetary returns to different college majors from a sample of Northwestern University undergraduates. He uses the data to study gender differences in observed college major choices and expectations formation by students.…”
Section: Recent Studies On Expectations For Schooling and Relatedmentioning
confidence: 99%
See 1 more Smart Citation